Effects of social facilitation and observational learning on feeding behavior of the red winged black bird (Angelaius Phoeniceus) - Mason, Russell J.; Redringer, Russell F. Jr (1981)
In the presence of food-deprived and therefore rapidly feeding Red-winged Black- birds (Agelaius phoeniceus), pairs of nondeprived conspecifics increased their own food consumption and spillage. The effect of social facilitation appeared amplified when both pairs of birds were food-deprived. Blackbirds also showed clear differential preferences for novel foods based on observations of male conspecifics consuming and spilling novel food. Social facilitation of feeding and observational learning of differential food preferences for novel foods may help to explain the Red-winged Blackbird's tendency to locate and exploit (i.e. damage) crops during short periods when the crops are especially vulnerable.